Environmental Fiscal Strategies: The Potential of Timber Excise to Address Deforestation and Increase State Revenues in Indonesia - Hazmi, Raldin; Rexipal, Dewangga; Wardana, Muhammad Fadhil Kusuma; Aji, Anggit Kuncoro; Walzer, Michael; Zahrurrijal, Muadz Muawwidz (Journal of Local Government Issues, 2025)
This study examines the feasibility of imposing an excise tax on timber products from forest logging activities in Indonesia, using a systematic literature review and a quantitative simulation approach. Data from Statistics Indonesia (BPS) on timber production between 2020-2023 are utilized to assess the potential impact of such a policy. The study argues that wood, as a key forest product, meets the criteria for being an Excisable Good (BKC) due to its consumption needing control, its environmental impacts, and the need for state levies. Additionally, it highlights the urgency of introducing this tax to address deforestation and generate additional state revenue. The research also presents various simulated excise rates to estimate the policy's economic effect. This study contributes to the literature on new BKC imposition and provides fiscal policy recommendations aimed at tackling deforestation, offering advice to the Ministry of Environment and Forestry and the Ministry of Finance on the implementation of timber excise.